Investigating the Lexical Demands of English-as-an-Additional-Language and General-Audience Podcasts and Their Potential for Incidental Vocabulary Learning - Motamedynia, Masoud; Nasrollahi Shahri, Naseh (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
This study investigated the lexical demands of English-as-an-additional-language (EAL) and general-audience podcasts and their potential for incidental vocabulary learning. Two corpora (i.e., one EAL and one general-audience) comprising 1,188,512 tokens were analyzed to determine the necessary vocabulary knowledge to reach 90% and 95% coverage. The results indicated that 2,000 and 3,000 word families plus proper nouns (PN), marginal words (MW), transparent compounds (TC), and acronyms (AC) covered 90% and 95% of words in podcasts, respectively. The results also showed that EAL and general-audience podcasts required 1,000 and 2,000 words families to reach 90% coverage, respectively. Regarding 95% coverage, knowledge of 2,000 (EAL) and 3,000 (general-audience) word families was required. The results also demonstrated almost 60% of word families from the 2,000-word level were encountered 15+ times in each corpus, suggesting podcasts may hold relatively great potential for learning such words incidentally. Furthermore, our findings indicated that there was some potential for incidentally learning words from the 3,000-word level in both corpora, while general-audience podcasts may hold greater potential in this regard. Implications for using podcasts in language pedagogy are also discussed.